Factors influencing cycle-by-cycle combustion characteristics of a diesel engine under cold idling conditions - McGhee, Michael James (2013)
An experimental investigation of post-start cold idling behaviour has been carried out on a modern single-cylinder HPCR DI light duty diesel engine with a low compression ratio of 15.5:1 at temperatures between 10 and -20°C. The trend toward lower compression ratios from more common values of around 22:1 a few years ago has resulted in lower compression pressures and temperatures, which negatively affects cold idle operation. Improvements in cycle-by-cycle stability of indicated work output through fuel injection strategy and glow plug temperature changes have been explored. This is important to improve NVH and the consumer’s perception of vehicle quality. The key effects on heat release characteristics have been identified and the associated impact on stability discussed. High speed imaging of ignition in a combustion bomb has been used to aid interpretation of engine results.